Decentralised management of drug-resistant tuberculosis (MDR- and XDR-TB) in South Africa: an alternative model of care. - Padayatchi, N; Friedland, G (The international journal of tuberculosis and lung disease : the official journal of the International Union against Tuberculosis and Lung Disease, 2008)
A growing number of cases of extensively drug-resistant tuberculosis (XDR-TB) have been reported from KwaZulu-Natal, South Africa.
Keywords: Humans; Models, Theoretical; Public Health Practice; South Africa; Tuberculosis, Multidrug-Resistant